Connection Between Resistance to Organizational Change and Psychological Resistance of an Individual - Prib, Hlib A.; Gromova, Zlata V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Resistance to organizational change as a facet of psychological resistance of an individual is a widespread phenomenon through which countries, organizations and individuals suffer significant losses. The increasing amount of articles and scientific papers researching the phenomenon of change resistance published for the past 50 year serves as an indicator that the problem of people resisting the implementation of change has not yet been fully studied. Yet the relevance of the issue is far from decreasing as companies keep sustaining considerable losses with the desired changes failing to be implemented as suggested by multiple studies. We believe there is an insufficiently researched aspect of this issue. The purpose of the article is to establish a clear connection between resistance to organizational change and psychological resistance. We believe that such a connection attesting to change resistance being a psychological phenomenon will shift the focus of future research from the organizational or managerial standpoint to viewing change resistance in a psychological dimension. A thorough analysis of previously conducted studies serves as a basis for revealing commonalities between the reason for change resistance and psychological resistance. A chart representing own classification of the reasons for change resistance and psychological resistance illustrating the similarities of the two phenomena can be found in the article. The present study further explores the connections of various strengths that can be seen between the two phenomena and proposes a summary spreadsheet demonstrating the research findings. The article concluded a comparative classification of the reasons for PR and RC appearance, it was stated the connections differ in terms of strengths and permanence.